Pressureless sintering, mechanical properties and oxidation behavior of ZrB2 ceramics doped with B4C. Issue 10 (September 2015) - Ma, Hai-Bin; Liu, Hu-Lin; Zhao, Jian; Xu, Fang-Fang; Zhang, Guo-Jun
Abstract A pressureless sintering process using different amounts of boron carbide (B4C) as sintering aid was investigated for the densification of zirconium diboride (ZrB2). The sintering mechanism was converted from solid state sintering to liquid phase sintering as sintering temperature increased from 2150 to 2250 °C. B4C addition improved densification by removing the oxide impurities during solid state sintering. Besides, it could restrain the growth of ZrB2 grains. At 2250 °C, ZrB2 and B4C formed liquid phase which was well wetting ZrB2 grains during liquid phase sintering process. The different roles of B4C on the microstructure development, mechanical properties and oxidation resistance of the sintered ZrB2-based ceramics were investigated.